2016
DOI: 10.1146/annurev-arplant-043015-111804
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Meiotic Anther Development: Cell Fate Specification and Differentiation

Abstract: Research into anther ontogeny has been an active and developing field, transitioning from a strictly lineage-based view of cellular differentiation events to a more complex understanding of cell fate specification. Here we describe the modern interpretation of pre-meiotic anther development, from the earliest cell specifications within the anther lobes through SPL/NZZ-, MSP1-, and MEL1-dependent pathways as well as the initial setup of the abaxial and adaxial axes and outgrowth of the anther lobes. We then con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 117 publications
0
86
0
1
Order By: Relevance
“…Cell signaling has been studied extensively in the context of many physiological and developmental processes, but little is known about how signal transduction pathways regulate somatic and reproductive cell differentiation in plants (Zhao et al, 2002;Jia et al, 2008;Zhao, 2009;Feng et al, 2013;Huang et al, 2016c;Walbot and Egger, 2016). So far, most identified ligands for functionally studied LRR-RLKs are small molecules and oligopeptides (Fletcher et al, 1999;Wang et al, 2001;Matsubayashi et al, 2002;Tang et al, 2002;Caño-Delgado et al, 2004;Kinoshita et al, 2005;Ito et al, 2006;Kondo et al, 2006;Stenvik et al, 2008;Shimada et al, 2011;Lee et al, 2012;Torii, 2012;Butenko et al, 2014;Huang et al, 2014;Matsubayashi, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell signaling has been studied extensively in the context of many physiological and developmental processes, but little is known about how signal transduction pathways regulate somatic and reproductive cell differentiation in plants (Zhao et al, 2002;Jia et al, 2008;Zhao, 2009;Feng et al, 2013;Huang et al, 2016c;Walbot and Egger, 2016). So far, most identified ligands for functionally studied LRR-RLKs are small molecules and oligopeptides (Fletcher et al, 1999;Wang et al, 2001;Matsubayashi et al, 2002;Tang et al, 2002;Caño-Delgado et al, 2004;Kinoshita et al, 2005;Ito et al, 2006;Kondo et al, 2006;Stenvik et al, 2008;Shimada et al, 2011;Lee et al, 2012;Torii, 2012;Butenko et al, 2014;Huang et al, 2014;Matsubayashi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The anther, where male gametophytes (pollen) are produced, typically has four lobes (microsporangia; Goldberg et al, 1993;Scott et al, 2004;Zhao, 2009;Feng et al, 2013;Walbot and Egger, 2016). Within each of these lobes in a mature anther, the central reproductive microsporocytes (or pollen mother cells) are surrounded by four concentrically organized somatic cell layers: epidermis, endothecium, middle layer, and tapetum (Zhao et al, 2002;Zhao, 2009).…”
mentioning
confidence: 99%
“…Early anther development is a complex event characterized by rapid cell 410 division and fate specification to support the development of functional anther 411 layers that are properly organized within the anther (Walbot and Egger, 2016;412 Zhang and Yang, 2014). In this study, we revealed that OsERS1, a 413 glutamyl-tRNA synthetase, functions in early anther cell division and patterning, 414 likely through maintaining physiological homeostasis of amino acids and 415 carbohydrate metabolism as well as redox status (Fig.…”
Section: Altered Redox Status Affects Early Anther Development 359mentioning
confidence: 99%
“…Tapetum consists of a monolayer or multilayers of cells, which surround successive stages of microsporocytes, tetrads, microspores, and developing pollen as anther development progresses [3032]. Tapetum development comprises three stages: differentiation, maturation, and programmed cell death (PCD).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis ) and monocots (e.g. maize and rice) employ similar, but also many different genes to control tapetum development [32, 37]. The ms8 mutant was isolated from the mutant library derived from BTx623 that has been used to generate the sorghum genome sequence [4].…”
Section: Discussionmentioning
confidence: 99%